2022
DOI: 10.1039/d1fo02216d
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of chicoric acid in a mouse model of Parkinson's disease involves gut microbiota and TLR4 signaling pathway

Abstract: Chicoric acid (CA), a polyphenolic acid obtained from chicory and purple coneflower (Echinacea purpurea), has been regarded as nutraceutical to combat inflammation, virus and obesity. Parkinson’s Disease (PD) is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…In PD, the imbalance of the microbiome-gut-brain axis plays a pivotal role [11], and gut microbial dysbiosis could conduce to the changes of metabolites, such as SCFAs, which might be one of the major mediators of neuroinflammation and gut inflammation [12,20]. In our previous work, we observed that CA showed a modulatory effect on gut microbiota and reduced gut inflammation [34], indicating that the gut is a crucial participant in PD. In the current study, transcriptome analysis was performed to examine the impact of CA on the gut in PD mice.…”
Section: Discussionmentioning
confidence: 88%
“…In PD, the imbalance of the microbiome-gut-brain axis plays a pivotal role [11], and gut microbial dysbiosis could conduce to the changes of metabolites, such as SCFAs, which might be one of the major mediators of neuroinflammation and gut inflammation [12,20]. In our previous work, we observed that CA showed a modulatory effect on gut microbiota and reduced gut inflammation [34], indicating that the gut is a crucial participant in PD. In the current study, transcriptome analysis was performed to examine the impact of CA on the gut in PD mice.…”
Section: Discussionmentioning
confidence: 88%
“…However, the results of studies on Ruminococcaceae in PD have been controversial and might be related to the disease duration of PD [ 60 ]. ASF356 and Acetatifactor belong to the Lachnospiraceae family and recent studies have revealed that the abundance of the Lachnospiraceae and Ruminiclostridium were decreased, whereas those of Alistipes and phylum Bacteroidetes were increased in MPTP-induced PD-like mice [ 61 , 62 , 63 ]. In 2020, Zhang et al identified Adlercreutzia , a genus associated with anti-inflammatory properties, as one of the PD-associated bacterial taxa in patients with PD [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…150 The presence of chicoric acid significantly reduced gut microbiota dysbiosis in PD mice and partially restored the normal production of short-chain fatty acids, thereby improving the integrity of the intestinal barrier. 149 In mice, supplementation with caffeic acid (251 mg/kg) also maintained the integrity of the intestinal barrier to some extent by reducing the disruption of tight junction proteins (ZO-1, occludin and claudin-1) that maintain intestinal barrier function. 151 Further studies found that pro-inflammatory cytokines such as TNF-α and IL-1β were reduced by chicoric acid in serum, striatum and colon, and that chicoric acid probably prevented neuroinflammation and intestinal inflammation by inhibiting the TLR4/MyD88/NF-κB signaling pathway.…”
Section: Autophagy Regulation By Hydroxycinnamic Acid Derivativesmentioning
confidence: 99%
“…151 Further studies found that pro-inflammatory cytokines such as TNF-α and IL-1β were reduced by chicoric acid in serum, striatum and colon, and that chicoric acid probably prevented neuroinflammation and intestinal inflammation by inhibiting the TLR4/MyD88/NF-κB signaling pathway. 149 Similarly, ferulic acid can affect the composition and structure of the intestinal microbiota. 152 In high-fat diet-induced mice, 100 mg/kg ferulic acid improved gut microbiota imbalance induced by high-fat diet, significantly increased intestinal short-chain fatty acids accumulation, reduced endotoxin-inducing bacteria, and inhibited the colonic TLR4/NF-κB pathway, alleviating colonic barrier dysfunction and intestinal inflammation.…”
Section: Autophagy Regulation By Hydroxycinnamic Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation